2019
DOI: 10.1123/tsp.2018-0126
|View full text |Cite
|
Sign up to set email alerts
|

Diversity Characteristics and Experiences of Discrimination in Certified Mental Performance Consultants

Abstract: The purpose of the present study was to explore diversity characteristics and experiences of discrimination in certified mental-performance consultants (CMPCs). The results of a questionnaire (N = 260) indicated that CMPCs remain a rather homogeneous population (>80% White, heterosexual, and able-bodied). Female and non-White consultants were significantly more likely to experience discrimination in the field. The findings indicate that minorities remain underrepresented among CMPCs. In addition, the profes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…Indeed, 92% of participants in the current study self-identified as White Caucasian. In a recent study, McCarver et al (2019) showed how SPPs are a relatively homogeneous group in that they are mostly White, heterosexual, and able-bodied. This homogeneity may prevent the profession from engaging in reflective efforts focused on Whiteness, privilege, and power, potentially fostering the promotion and maintenance of color-blind approaches to the field and profession and sport contexts in general (Blodgett et al, 2015, Butryn, 2002, 2009; Sue, 2004).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, 92% of participants in the current study self-identified as White Caucasian. In a recent study, McCarver et al (2019) showed how SPPs are a relatively homogeneous group in that they are mostly White, heterosexual, and able-bodied. This homogeneity may prevent the profession from engaging in reflective efforts focused on Whiteness, privilege, and power, potentially fostering the promotion and maintenance of color-blind approaches to the field and profession and sport contexts in general (Blodgett et al, 2015, Butryn, 2002, 2009; Sue, 2004).…”
Section: Resultsmentioning
confidence: 99%
“…Another potential challenge to the integration of culture may be the specific professional spaces in which SPPs work. The SP professional context is widely characterized by homogeneity and Whiteness, both in terms of SPP demographic characteristics as well as the Westernized frameworks used to evaluate the validity and effectiveness of scholarly products and applied interventions (Blodgett et al, 2015; Butryn, 2002; 2009; McCarver et al, 2019; Ryba, 2017). This homogeneity may lead to a persistent color-blind worldview in the SP field and profession, and in sport as a whole (Blodgett et al, 2015).…”
mentioning
confidence: 99%
“…This barrier parallels the lack of cultural diversity seen across SPCs, particularly those with a Certified Mental Performance Consultant (CMPC) credential. 23 Professional organizations such as AASP must continue to promote diversity and inclusion practices and address barriers for diverse practitioners to work in the field. 23 Improving representation of SPCs across minority groups (i.e.…”
Section: Attitudes and Beliefsmentioning
confidence: 99%
“…23 Professional organizations such as AASP must continue to promote diversity and inclusion practices and address barriers for diverse practitioners to work in the field. 23 Improving representation of SPCs across minority groups (i.e. racial/ethnic minorities, women 23 ) may help to address some of these barriers identified by high school coaches.…”
Section: Attitudes and Beliefsmentioning
confidence: 99%
“…Homogeneity is dangerous as it can contribute to ethnocentric monoculturalism in which the dominant cultural views appear truthful and common sense (Sue, 2004). For example, McCarver et al (2019) found that over 80% of CMPCs identify as white, heterosexual, and able-bodied. Likewise, the results in the current study suggest that SEP was founded upon, and continuously operates from, a Eurocentric and white worldview, which perpetuates the exclusion and harm of traditionally marginalized populations and raises serious doubts that knowledge presented at AASP is relevant and generalizable to all (Ryba & Schinke, 2009;Ryba et al, 2013;Ryba et al, 2020).…”
Section: Cultural Diversity Content In Presentation Abstractsmentioning
confidence: 99%